Size and Shape of Plots and Blocks for Field Experiments in Natural Grasslands in Chambal Ravines of South- Eastern Rajasthan - Aggarwal, M C; Parindyal, A K; Kumar, Nirmal; Singh, K D (Annals of Arid Zone, 2016)
A uniformity trial conducted 011 natural grasslands of Chambal ravines revealed that .the coefficient of variation decreased with the increase in plot size up to 12 m2 . The equation Y = aX-b gave a good fit to Â·the relationship between coefficient of variation (Y) and plot sizes (Xl. Plot shape had no effect on coefficient of variation. however. plot elongated towards column had shown smaller coefficient of variation. The number of replications indicated that the plot size of 8 to 12 m2 was suitable. The block efficiency decreased with an increase in block size. The shape of the block had no effect on coefficient of variation. However. the blocks elongated towards rows were found to be more efficient. The relationship (Y = aX-b) between coefficient of variation (Y) and block size (X) was also filled to various plot sizes and shapes.